Nugget Jamur Kuping dan Ekstrak Kulit Buah Naga Merah Sebagai Pangan Diet Vegetarian Tinggi Serat - Alfin Nur Adiningsih; Nuraeni, Indah; Ramadhan, Gumintang Ratna (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Number of vegetarians in Indonesia is rising. This increase may be attributed to improvement of people knowledge regarding health benefits of high fiber plant-based diet especially to reducing the risks of degenerative diseases. However, high fiber plant-based food especially mushroom-based food that being accepted by majority of panelists are limited to oyster and straw mushroom. Hence, the goal of this research is to get the best formula based on organoleptic and crude fiber content from Auricularia polytricha and red dragon fruit peel extract as a food for vegetarian diet. This study used experimental study with Randomized Block Design (RBC) method with two experimental factors: the concentration and volume of red dragon fruit peel extract (25 ml and 50 ml) and the proportions of wheat flour and Auricularia polytricha (30:70, 50:50, 70:30). Organoleptic test results data were analyzed using the Krusskal Wallis test and the Man-Whitney U test to test it further. The results showed that there was a significant effect of the nugget ingredient formulation on color, taste, and texture of the nuggets (p<0,05), and there was no significant effect on the aroma of the nuggets (p>0,05). The highest crude fiber content was found in nuggets with a composition of 70% Auricularia polytricha and 30% wheat flour with the addition of 50 ml red dragon fruit peel extract, which was 36.88%, and anthocyanin content of 0,99 mg/100 g. The best formula for Auricularia polytricha nuggets with the addition of red dragon fruit peel extract is J3E2 with a composition of 70% Auricularia polytricha and 30% wheat flour and the addition of 50 ml of red dragon fruit skin extract.